Changes in resting EEG following methadone treatment in opiate addicts. Issue 5 (May 2015) - Wang, Grace Y.; Kydd, Rob; Wouldes, Trecia A.; Jensen, Maree; Russell, Bruce R.
Highlights There are methadone-related changes on resting EEG. The abnormal neural electrical activity present in those still using illicit opiates might be reduced following methadone maintenance treatment (MMT). The present findings provide further support for MMT of opiate dependence and demonstrates potentially positive effects of substitution treatment on brain function.